2007
DOI: 10.1021/ja0690464
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of a Histidine Copper Ligand in Fern Plastocyanin

Abstract: Plastocyanin is a small blue copper protein that shuttles electrons as part of the photosynthetic redox chain. Its redox behavior is changed at low pH as a result of protonation of the solvent-exposed copper-coordinating histidine. Protonation and subsequent redox inactivation could have a role in the down regulation of photosynthesis. As opposed to plastocyanin from other sources, in fern plastocyanin His90 protonation at low pH has been reported not to occur. Two possible reasons for that have been proposed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…A similar behavior was reported for plastocyanin from a fern plant and explained by π-π interactions with a phenylalanine replacing Leu12 [41]. This observation later was contradicted on the basis of mutant structures [42]. In PCa and PCb, His87 is located in an essentially identical structural environment, which is not affected by replacements.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar behavior was reported for plastocyanin from a fern plant and explained by π-π interactions with a phenylalanine replacing Leu12 [41]. This observation later was contradicted on the basis of mutant structures [42]. In PCa and PCb, His87 is located in an essentially identical structural environment, which is not affected by replacements.…”
Section: Discussionsupporting
confidence: 64%
“…Investigations of the physico-chemical characteristics of PCa and PCb [14][15][16][17][18][19] and studies of PC mutants in transgenic Arabidopsis plants [20] pointed to differences in the roles of the simultaneously acting iso-proteins in the photosynthetic electron-transport chain. In particular, the isoforms were found to exhibit different ionization properties of a conserved acidic patch (residues [42][43][44] [16], which is involved in the interaction with PSI [21]. Preliminary data from flash-photolysis experiments showed that fast electron transfer occurred between both poplar PC isoforms and spinach PSI-particles, whereby the rate of electron transfer to PSI differed between PCa and PCb (H. Bottin, personal communication to M.I.D).…”
Section: Introductionmentioning
confidence: 99%
“…To study the three Pcs by NMR, the proteins were isotopically labeled with 15 [31] and Cu I -PoPc (BMRB code 4019) were used as the starting points. Data for backbone assignments (H, N, C a , C b ) have been deposited to BMRB under codes 19236 (DPc) and 19247 (PoPc).…”
Section: Backbone Assignmentsmentioning
confidence: 99%
“…[23][24][25] As far as electronic spectra are concerned, research has been stimulated in the past years by the X-ray crystal structure determination of several chromophore-containing and light-sensitive biomolecular systems. Important examples include the green fluorescent protein (GFP) [26,27] occurring in bioluminescent organisms and now widely used as a fluorescence label, [28] blue copper proteins like plastocyanin, [29,30] which is involved in electron shuttling in photosystem I (PSI), and photoreceptor proteins like phytochromes, [31][32][33][34] the photoactive yellow protein (PYP), [35,36] the visual pigment rhodopsin, [37,38] or the light-driven proton pump bacteriorhodopsin. [39,40] The systems acting as photoreceptors typically undergo photochemically initiated cis-trans (or transcis) isomerizations, as is the case in the photoisomerization of retinal in the primary step in vision, and in light-driven signaling processes as occurring in PYP and in phytochromes.…”
Section: Introductionmentioning
confidence: 99%